Analisis Deiksis pada Daftar Putar Belajar Mantappu dalam Channel Youtube Nihongo Mantappu - Muhammad Fadil Mubarok; Rifqi Daffa Alghifari; Moh Aulina Ahsanul Haq; Fairuz Pandu Rahagi; Bagas Faudzul Adzim; Bagas Agung Alamsyah; Asep Purwo Yudi Utomo (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Deixis is a word that refers or leads to something that is influenced by the speaker's situation, deixis has a function according to its respective reference according to the context. The purpose of the research is to describe persona deixis, place deixis, time deixis, discourse deixis, social deixis in conversations on the Nihongo Mantappu YouTube channel. The method used in this paper is descriptive qualitative method. Based on the analysis, the researcher has found 4 forms of deixis in the data that has been studied, these deixis include persona deixis, place deixis, discourse deixis, and social deixis. The most frequently used deixis is discourse deixis in the form of this word. The use of discourse deixis is most often used because Jerome Polin or his friends more often mention this word because it refers to the discussion discussed, namely the Indonesian writing and speaking test by foreigners or foreigners. Each deixis found has its own function depending on the context. The research that has been done is interesting because the videos analyzed have sources from abroad and the benefits of this research are expected to help readers understand what deixis are found in the videos that researchers analyze.